Aspekty organizacyjno-prawne systemu informacyjnego rządowej administracji skarbowej - Gadomski, Sebastian (Organization and legal aspects of the information system of governmental revenue administration, 2005)
In this article the author defines the information system of governmental revenue administration.The structure and division of revenue administration in Poland has been characterized here. Next an attempt is made to identify the information system of the governmental revenue administration. Here the components as well as some of the user groups of this system have been shown. The environment have been also characterized (with exposing the legal environments), which essentially influence the shape of the information system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 13-26